The Influence Of Digital Transformation, Internal Control and Earning Management on Tax Avoidance - Amanda, Jessica; Maryati, Sri; Patmawati, Patmawati (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2025)
This study aims to analyze the influence of digital transformation, internal control, and earning management on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The approach used is quantitative using secondary data obtained from the company's annual report. The analysis technique used is multiple linear regression with the help of SPSS version 27. The results of the study indicate that earning management and simultaneously have a significant effect on tax avoidance, while digital transformation and internal control do not show a significant effect partially on tax avoidance. The results of the study are expected to provide insight into how the adoption of digital technology and strengthening internal control systems can minimize tax avoidance practices, as well as how discretionary accruals can affect corporate tax decisions.